2012
DOI: 10.1130/g33178.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival of a submarine canyon during long-term outbuilding of a continental margin

Abstract: Net-depositional submarine canyons are common in continental slope strata, but how they survive and prograde on constructional margins is poorly understood. In this study we present fi eld evidence for the coevolution of a submarine canyon and the adjacent continental slope. Using a three-dimensional seismic data cube that images the Ebro margin (northwest Mediterranean), we identify a preserved canyon on a middle Pleistocene paleosurface and relate it directly to its expression on the present-day seafl oor. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Some authors have proposed a similar process to explain the origin of submarine canyons [e.g., Farre et al, 1983;Pratson and Coakley, 1996;Micallef et al, 2014]. The progression from numerous small canyons to fewer large canyons has been documented in 3-D seismic images of the subsurface [e.g., Kertznus and Kneller, 2009;Amblas et al, 2012]. As interpreted in these field studies, the evolution in our experiments results from the progressive capture of cross-shelf flows by the surviving canyons, which in turn causes them to deepen and widen as they capture additional tributaries in their upper reaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have proposed a similar process to explain the origin of submarine canyons [e.g., Farre et al, 1983;Pratson and Coakley, 1996;Micallef et al, 2014]. The progression from numerous small canyons to fewer large canyons has been documented in 3-D seismic images of the subsurface [e.g., Kertznus and Kneller, 2009;Amblas et al, 2012]. As interpreted in these field studies, the evolution in our experiments results from the progressive capture of cross-shelf flows by the surviving canyons, which in turn causes them to deepen and widen as they capture additional tributaries in their upper reaches.…”
Section: Discussionmentioning
confidence: 99%
“…They appear on both active and passive margins and provide a critical pathway for terrestrial sediment delivery to the deep ocean [ Pratson et al , , and references therein]. The existence and scale of submarine canyons have long been recognized [ Shepard , ], but only in recent years—due largely to improvements in bathymetric imaging—has their resemblance to terrestrial river valleys and drainage systems been fully appreciated [e.g., Mitchell , ; Amblas et al , ; Brothers et al , ]. This observation suggests that the physical processes shaping submarine canyons have some basic similarities to those shaping subaerial landscapes, especially in their upper reaches where local slopes and heights above the basin floor are greatest.…”
Section: Introductionmentioning
confidence: 99%
“…Why does the Indus have this large canyon and what are its relations to the river mouth? The processes that form submarine canyons are not always clear because of the recognition that they may have multiple causes and because canyons remain active for long periods of geologic time and are thus subject to a variety of possible forcing processes (Shepard, ; Amblas et al ., ). As a result the reasons for their abandonment are also not universally understood.…”
Section: Introductionmentioning
confidence: 97%
“…Submarine channels have long been recognized in canyons, on fans, and across deep-sea plains and represent major conduits for sediment routing along continental margins. The planform geometry, deposits, and flow patterns of deep water sinuous channels have been examined using methods including sonar and in situ measurements [Deptuck et al, 2007;Kertznus and Kneller, 2009;Amblas et al, 2012;Wynn et al, 2014]. These studies identified distinctive features of submarine channels relative to rivers, including reversed helical flow patterns, ossification of channel mobility, comparable in-channel and overbank sedimentation rates, and the potential influence of Coriolis forces on channel sinuosity [Peakall et al, 2000;Wynn et al, 2007;Flood et al, 2009;Babonneau et al, 2010;Parsons et al, 2010;Kolla et al, 2012;Peakall et al, 2012;Sumner et al, 2014].…”
Section: Introductionmentioning
confidence: 99%